The impact of mental health literacy on professional psychological help-seeking attitudes among Chinese college students: the chain mediating role of anxiety and depression - Shi, Ke; Tian, Jinlai (Frontiers in Psychology, 2025)
By analyzing cross-sectional data from 2,078 college students, this study aims to explore the impact of mental health literacy on Chinese college students’ professional psychological help-seeking attitudes and to test the chained mediation role of anxiety and depression. Results show that mental health literacy significantly positively predicts professional psychological help-seeking attitudes. Anxiety and depression exhibit partial mediation effects, forming a chained mediation pathway, suggesting mental health literacy indirectly reduces depression by alleviating anxiety, enhancing professional psychological help-seeking attitudes. This study reveals the chained mechanism between anxiety and depression, addressing previous neglect of emotional factors, and highlights the core role of practical dimensions in mental health literacy. It is suggested that universities incorporate mental health literacy training into curricula, strengthen practical skill development, and design interventions for emotion regulation to disrupt the negative cycle of anxiety-depression. This study provides a theoretical basis and targeted strategies for optimizing psychological services for college students.